ZWIĄZKI SPÓŁDZIELCZE JAKO NARZĘDZIE WSPIERANIA SPÓŁDZIELNI SOCJALNYCH - Michalik, Andrzej (Zeszyty Prawnicze, 2016)
Cooperative Unions as an Instrument for the Support of Social Cooperatives in Poland Summary The article provides basic information on the evolution of cooperative unions in Poland. It shows the numerous advantages of membership of cooperative unions for individual cooperatives, which helps them on the road to economic and social success. This is particularly important for social cooperatives, whose aim is to act on behalf of their members’ social and professional reintegration. The article describes the Polish union of social cooperatives, the country’s only representative body for social cooperatives with the legal authority to act as a partner in discussions and negotiations with administrative bodies on new legislation relating to social cooperatives. The article is supplemented with a set of proposals concerning cooperative unions for the legislator’s consideration in the draft of a new act on the cooperative movement.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />